A note on mixed summation-integral-type operators - Gupta, M.K.; Manoj Kumar; Rupen Pratap Singh (Український математичний журнал, 2007)
Very recently Deo, in the paper “Simultaneous approximation by Lupas operators with weighted function of Szasz operators” [J. Inequal. Pure Appl. Math., 5, No. 4 (2004)] claimed to introduce the integral modifications of Lupas operators. These operators were first introduced in 1993 by Gupta and Srivastava. They estimated the simultaneous approximation for these operators and called them Baskakov-Szasz operators. There are several misprints in the paper by Deo. This motivated us to perform subsequent investigations in this direction. We extend the study and estimate a saturation result in simultaneous approximation for the linear combinations of these summation-integral-type operators. Нещодавно Део у роботі "Simultaneous approximation by Lupas operators with weighted function of Szasz operators" (J. Inequal. Pure and Appl. Math., 2004, Vol. 5, № 4) заявив про введення ним інтегральних модифікацій операторів Лупаса. Вперше такі оператори ввели Гупта та Шрівастава у 1993 р. Вони оцінили одночасне наближення цих операторів та назвали їх операторами Васкакова - Шаша. У роботі Део є кілька неточностей. Це спонукало авторів продовжити дослідження у згаданому напрямі. У даній статті розширено коло досліджень та отримано оцінку результату щодо насичення при одночасному наближенні для лінійних комбінацій цих операторів сумовно-інтегрального типу.